Primary production and chlorophyll in the Barents Sea in September-October, 1997. - Vedernikov, Vladimir I; Gagarin, Vladimir I (PANGAEA, 1998)
The described studies were carried out in the eastern part of the sea during the end of the summer seasonal succession from September 1 to October 12, 1997. Concentration of chlorophyll a in the surface layer varied from 0.09 to 1.24 mg/m**3; it tended to increase in the southern regions (<74°N). Primary production in the water column (P_p) varied from 24 to 214 mg C/m**2/day and was on average 91 mg C/m**2/day. The low level of P_p seems to result from combination of physical and chemical environmental factors unfavorable for photosynthesis (e.g. deficiency of nutrients and low values of insolation and temperature) and intensive grazing of phytoplankton by zooplankton. The lower boundary of the photosynthetic layer in open waters was located at depth 60-75 m; irradiance there was 0.1-0.5% of incident irradiance. In deep-water regions (>200 m) the subsurface maximum of chlorophyll occurred in the layer at 20-40 m; usually this maximum resulted in formation of additional maxima of primary production.
(Table 1) Results of measurements of productive characteristics of phytoplankton and environmental parameters in the Barents Sea in September-October 1997
Keywords: 14C in-situ incubation; Akademik Sergey Vavilov; Archive of Ocean Data; ARCOD; Assimilation rate of carbon per chlorophyll a; ASV11; ASV11-1067P; ASV11-835P; ASV11-860P; ASV11-875P; ASV11-891P; ASV11-966P; ASV11-991P; Barents Sea; Chlorophyll a; Date/Time of event; Depth of Secchi Disk; Fluorometry; MULT; Photometry; Photosynthesis layer, thickness; Primary production, integrated; Primary production of carbon; Secchi disc; Solar radiation; Temperature, water; Thermometer